Infuential factors in learning through the metaverse in secondary education students - López-Belmonte, Jesús; Pozo-Sánchez, Santiago; Moreno-Guerrero, Antonio-José; Lampropoulos, Georgios (Revista Complutense de Educación, 2025)
The metaverse is positioning itself as an emerging technology in the field of education. The objective of this study focuses on analyzing the influence of various exogenous and endogenous factors on students’ learning outcomes through educational activities in the metaverse. A descriptive and correlational research design was used for this investigation. The sample consisted of 923 Spanish secondary education students. Data collection was carried out through the METAEDU questionnaire. The results reveal that variables such as gender and age have an impact on motivation, interest, and learning outcomes. Similarly, the widespread use of ICT (Information and Communication Technology) enhances technology interaction, accessibility, proficiency, as well as students’ interest and motivation. The educational use of ICT has benefited aspects such as the inherent possibilities of the metaverse and other components like interaction, interest, motivation, and student learning. However, playing virtual reality games does not affect student-generated learning. In conclusion, the findings confirm the hypotheses raised, highlighting the positive impact of technology interaction, intrinsic possibilities, accessibility, motivation, and interest on student learning in the metaverse.